Efavirenz Therapeutic Range in HIV-1 Treatment-Naive Participants. Issue 6 (December 2017) - Bednasz, Cindy J.; Venuto, Charles S.; Ma, Qing; Daar, Eric S.; Sax, Paul E.; Fischl, Margaret A.; Collier, Ann C.; Smith, Kimberly Y.; Tierney, Camlin; Yang, Yang; Wilding, Gregory E.; Morse, Gene D.
Abstract : Background: Efavirenz is currently suggested as an alternative to recommended antiretroviral (ARV) regimens by the Department of Health and Human Services for the treatment of HIV-1 in ARV-naive patients. A mid-dosing interval therapeutic range between 1000 and 4000 ng/mL for efavirenz has been proposed in the literature, with patients more likely to experience virologic failure below this range and adverse effects above. The current study reports an analysis of virologic outcome between those above, below, or within the reported efavirenz therapeutic range (1000–4000 ng/mL) and within subgroups. Methods: This analysis examined efavirenz plasma concentrations obtained from participants enrolled in AIDS Clinical Trials Group Study A5202. This investigation divided subjects into those who experienced virologic failure and those who did not. These subjects were further separated to investigate those who had "high, " "within, " or "low" plasma concentrations, based on the therapeutic range. The association between virologic failure and plasma concentration was statistically examined in addition to the variables: race/ethnicity, sex, assigned nucleos(t)ide reverse transcriptase inhibitor backbone, age at study entry, history of intravenous drug use, weight, and screening HIV-1 RNA stratification level. Results: In univariate analyses, a statistically significant difference was found when comparing the efavirenz concentration groups, (22 failures among the "low" concentration group [19%], 65 failures among the "within" concentration group [12%], and 11 failures among the "high" concentration group [9%]) when evaluating virologic failure as an outcome ( P = 0.04). In addition, the proportion of participants with virologic failure differed across race/ethnicity groups ( P = 0.03) with black non-Hispanic participants observed to have the highest rate (17%). Efavirenz concentration group, race/ethnicity, age, weight, and the interaction between efavirenz concentration group and weight were found to be significantly associated with virologic failure in multivariable logistic regression analysis. Conclusions: The proposed efavirenz therapeutic range, combined with the impact of a patient's weight, is associated with virologic failure in HIV-infected ARV-naive individuals in the United States. Additional analysis is recommended to determine the most appropriate concentration value that defines the lower limit of the efavirenz therapeutic range.